Analysis of Indicators of Constitutional Decline in Indonesia (A Review of Contemporary Democracy) - Hapsoro, Fakhris Lutfianto; Rofiqi, Moh. Hasbi (PT. Multidisciplinary Press Indonesia, 2024)
The constitutional erosion in Indonesia is an important topic in the present political and legal climate, and this study intends to examine it. In this study, we apply Aziz Huq and Tom Ginsburg's five indicators to the question of why our country's democracy and constitutional institutions have crumbled. A qualitative strategy was employed for the study, which included gathering information from pertinent books and court records. Democracy in Indonesia has taken a major step back, according to the study's findings. Deterioration of democratic institutions like the Corruption Eradication Commission (KPK) and the Constitutional Court (MK) is one of these findings. Another is the distortion of the system of checks and balances among the executive, legislative, and judicial branches. Lastly, there has been an upsurge in attacks on civil liberties and public spaces. The study also shows that constraints on civil society groups' operations and political and societal pressure on free speech make matters worse. This research proves that our justice system needs major overhauls to make it more open and accountable, safeguard our rights to free speech and assembly, and improve the quality of law enforcement. In light of the difficulties encountered by Indonesian democracy, this study adds to our knowledge of the subject and offers practical solutions to the problem, with the ultimate goal of halting the country's constitutional collapse and ensuring the continuity and growth of Indonesian democracy.